Pengembangan Model STEAM (Science, Technology, Engineering, Art, and Mathematics) untuk Meningkatkan Literasi Sains Siswa Sekolah Dasar - Insani Juniarti; Sukardi; Syaiful Musaddat (Postgraduate, University of Mataram, 2025)
This study aims to develop an integrated STEAM model of experiential learning and constructivism in improving elementary school students' scientific literacy. The sampling technique uses purposive sampling. Data collection techniques include interviews, questionnaires, and tests. Data processing is carried out using descriptive statistics. The development method used is design-based research (DBR), which has four stages; Stage 1, The preliminary study found challenges and problems regarding the implementation of the STEAM learning model in elementary schools. Stage 2, design and product development. Stage 3, involves a validation test involving five experts: technology, materials, language and two of education practitioners. The fourth stage is product improvement. The study results showed that the STEAM model met the criteria for being feasible and practical. The results of statistical testing using the T Test (Independent Sample T test) obtained a significance value of 0.001 <0.05. The effectiveness criteria were met with an average score of Ngain in the experimental class of 0.62 in the moderate category. The N Gain Percent test scored 62% with a reasonably moderate category. The STEAM model, integrated with constructivism and experiential learning, has proven effective in improving elementary school students' scientific literacy.